PENERAPAN AKUNTANSI NIRLABA DALAM RANGKA PENINGKATAN KELENGKAPAN PENYAJIAN INFORMASI LAPORAN KEUANGAN PADA GEREJA KRISTUS TUHAN (GKT) BANYUWANGI - Olivia Florendra Santoso; Eko Pudjolaksono (Perpustakaan Universitas Surabaya, 2018)
This study is a descriptive research. This study aims to examine the application of non-profit accounting in the financial statements of GKT Banyuwangi so as to improve the completeness of the information in the financial statements presented. This study is applied research that wants to solve the problem through a practical solution provided. Data collection techniques in this research is qualitative method. The method used is interview, observation, and document analysis. This research describes how the preparation of financial statements used by the organization today and review the weaknesses of the preparation of these financial statements. The preparation of financial statements used by the organizations today is a simple financial report. This financial statements has many weaknesses and not reliable in giving financial information. The findings of this study indicate that the non-profit accounting application can solve the problem of incomplete financial information contained in the financial statements of GKT Banyuwangi. This application of non-profit accounting can improve the completeness of the presentation of information in the financial statements and so that this church can present adequate financial information and support the church’s accountability to their congregation.